STRATEGI BERTAHAN UNTUK MERESPON PANDEMI COVID-19 PADA KEUANGAN UMKM TAHU “BINA USAHA TAHU” Pakunden Kota Blitar - Arif Wahyudi; Henni Indarriyanti (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2022)
The current Covid-19 pandemic is certainly very impactful for entrepreneurs, especially SMEs Tofu "Bina Usaha Tofu", one of the impacts is the reduced activity of buyers due to PPKM as it is today. Tofu UMKM certainly suffer losses, from the decline in buyers to limited supplies of raw materials. The impact of the COVID-19 pandemic will be fatal to financial problems and will affect a business such as continuous losses. For this reason, this researcher aims to find out how the survival strategy is to maintain financial stability in order to deal with the covid-19 pandemic used by UMKM Tofu "Bina Usaha Tahu" Pakunden Blitar City. This study uses qualitative research methods by approaching a study, namely interviews with resource persons as informants, and documentation as evidence of research results. The results of this study indicate that the survival strategy to respondto the covid-19 pandemic in tofu UMKM "Bina Usaha Tahu" is to reduce the amount of production in white tofu and process solid and liquid waste in tofu so that tofu waste is not wasted and can increase income and reduce environmental pollution.